Study And Evaluation Of Innovative Methods For Printing Solid Catalysts Intended For NOx Pollution Control - Chatziiona, Vasiliki K. (Faculty of Geotechnical Sciences and Environmental Management, Cyprus University of Technology, 2019)
The present Doctoral Dissertation concerns the evaluation and development of an innovative method for preparing solid supported-Pt catalysts intended for NOx pollution control. In particular, the alternative and cutting-edge approach of developing catalysts via multilayer inkjet printing was examined, so as to control the structure of solid catalysts at a nanoscale level, using two different printers, i.e., a modified Epson L800 printer and a commercial material printer (DMP-2850). For the first time ever, one 0.1 wt% Pt/MgO/CeO2 and two 0.1 wt% Pt/Al2O3 catalysts were prepared by novel inkjet printing and compared, in terms of their catalytic behaviour towards the NO/H2/O2 reaction, against four catalysts prepared by a standard and a modified wet impregnation method. It is worth mentioning that the inkjet-printed Pt/Al2O3 catalysts presented excellent activity and wide operating temperature window (TR=100-250oC) towards the selective catalytic reduction of NO by H2 under strongly oxidizing conditions (H2-SCR) in the very low-temperature range of 100-200ºC. Specifically, the Epson printed Pt/Al2O3 catalyst, presented XNO= 91% at 150oC, while the DMP printed Pt/Al2O3 catalyst presented an average XNO= 97% for the low-temperature range of 140-200oC and XNO= 99.5% at 175oC. As for the DMP inkjet-printed Pt/MgO/CeO2 catalyst, it showed remarkable catalytic performance (XNO= 100%, SN2= 100%, TR≥ 200oC) in the absence of oxygen (NO/H2 reaction), a result which has never been reported before, according to the author’s knowledge, in particular without the formation of NH3 as a by-product. Surface reactivity studies by transient methods performed within the present work indicated that the inkjet printing process leads to a unique surface structure of the printed catalysts that probably favours the formation of different intermediate NOx species, which are active at very low reaction temperatures. Moreover, it was proven through combined SSITKA-DRIFTS studies, that the different catalyst preparation methods utilized for the development of Pt/MgO-CeO2 catalysts, affects the formation and concentration of different active adsorbed intermediate NOx species on Pt surface, as well as on the support and the metal-support interphase. Furthermore, the transient experiments revealed important information towards the understanding of basic mechanistic issues of the present catalytic system (e.g., surface coverage of NOx intermediate species and N-containing species, H2 spillover).
Keywords: novel catalyst inkjet printing; supported Pt catalysts; H2-SCR; NO reduction